2016
DOI: 10.1080/13825585.2016.1244247
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between face recognition ability and socioemotional functioning throughout adulthood

Abstract: The relationship between face recognition ability and socioemotional functioning has been widely explored. However, how aging modulates this association regarding both objective performance and subjective-perception is still neglected. Participants, aged between 18 and 81 years, performed a face memory test and completed subjective face recognition and socioemotional questionnaires. General and social anxiety, and neuroticism traits account for the individual variation in face recognition abilities during adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Our participants performed all assessments remotely over the internet, and prior evidence indicates that the quality and reliability of data collected through the web is as good as that of data collected in the laboratory (Germine et al, 2012). Consistent with this finding, the magnitude of our correlation between CFMQ scores and objective facial recognition performance fell at the high end of the range of values previously reported for associations between subjective and objective measures in the laboratory-based studies of other research groups (Bindemann et al, 2014;Gray et al, 2017;Livingston & Shah, 2017;Rotshtein et al, 2007;Shah, Gaule, et al, 2015a;Shah, Sowden, et al, 2015b;Stollhoff et al, 2011;Turano et al, 2016;Turano & Viggiano, 2017). Nonetheless, one could speculate that the data for the participants we identified as having prosopagnosia might be uniquely suspect with respect to its quality, given that this subset of participants, by definition, constitutes the outliers, and that such poor performance could merely be caused by factors unrelated to facial recognition ability.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our participants performed all assessments remotely over the internet, and prior evidence indicates that the quality and reliability of data collected through the web is as good as that of data collected in the laboratory (Germine et al, 2012). Consistent with this finding, the magnitude of our correlation between CFMQ scores and objective facial recognition performance fell at the high end of the range of values previously reported for associations between subjective and objective measures in the laboratory-based studies of other research groups (Bindemann et al, 2014;Gray et al, 2017;Livingston & Shah, 2017;Rotshtein et al, 2007;Shah, Gaule, et al, 2015a;Shah, Sowden, et al, 2015b;Stollhoff et al, 2011;Turano et al, 2016;Turano & Viggiano, 2017). Nonetheless, one could speculate that the data for the participants we identified as having prosopagnosia might be uniquely suspect with respect to its quality, given that this subset of participants, by definition, constitutes the outliers, and that such poor performance could merely be caused by factors unrelated to facial recognition ability.…”
Section: Discussionsupporting
confidence: 83%
“…In an attempt to efficiently identify and study individuals with poor facial recognition abilities in a similar manner, several research groups have developed self-reported facial recognition ability questionnaires or clinical interviews, the scores of which have been reported to be associated with other measures of facial recognition performance (De Heering & Maurer, 2014;Kennerknecht et al, 2006;Kennerknecht, Plümpe, Edwards, & Raman, 2007;Palermo et al, 2017;Shah, Gaule, Sowden, Bird, & Cook, 2015a;Turano, Marzi, & Viggiano, 2016). Prior studies have reported moderate-tostrong correlations between self-reported face recognition abilities and objective performance, for typical participants (Bindemann, Attard, & Johnston, 2014;Gray, Bird, & Cook, 2017;Livingston & Shah, 2017;Rotshtein, Geng, Driver, & Dolan, 2007;Shah, Gaule, Sowden, Bird, & Cook, 2015a;Shah, Sowden, Gaule, Catmur, & Bird, 2015b;Turano et al, 2016;Turano & Viggiano, 2017;Wilmer et al, 2010; though see Palermo et al, 2017) as well as for those with developmental prosopagnosia (Livingston & Shah, 2017;Stollhoff, Jost, Elze, & Kennerknecht, 2011). The reported correlation magnitudes are usually in the range of .35 to .55.…”
mentioning
confidence: 99%
“…certain items in the PI20), and across all self-report instruments (e.g. those developed by de Heering & Maurer, 2012;Kennerknecht, et al, 2008;Palermo et al, 2017;Turano & Viggiano, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While some questionnaires have continued to offer only low-to-moderate correlations with objective measures of face recognition ability (e.g. Palermo et al, 2017;Turano & Viggiano, 2016), the 20-item Prosopagnosia Index (PI20; Shah et al, 2015) has fared more successfully.…”
Section: Prosopagnosia Severitymentioning
confidence: 99%
“…The PI20 was further validated against a measure of face-matching ability (Glasgow Face Matching Test; Burton, White, & McNeill, 2010) that is more representative of applied settings (Shah, Sowden, Gaule, Catmur, & Bird, 2015). Turano and colleagues (Turano, Marzi, & Viggiano, 2016; Turano & Viggiano, 2017) have since developed the Italian Face Ability Questionnaire, which successfully measures individual differences in face recognition ability in Italian samples (Turano et al, 2016; Turano & Viggiano, 2017).…”
mentioning
confidence: 99%